2020
DOI: 10.2196/18290
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Virtual Reality in Nursing Education: Meta-Analysis

Abstract: Background Virtual reality (VR) is the use of computer technology to create an interactive three-dimensional (3D) world, which gives users a sense of spatial presence. In nursing education, VR has been used to help optimize teaching and learning processes. Objective The purpose of this study was to evaluate the effectiveness of VR in nursing education in the areas of knowledge, skills, satisfaction, confidence, and performance time. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
207
5
11

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 299 publications
(231 citation statements)
references
References 50 publications
8
207
5
11
Order By: Relevance
“…Participants reported that VS was beneficial in helping them practice and gain competence and confidence to provide nursing care. Other studies have reported that VS offered students a positive experience ( Gu et al, 2017 ; Wright et al, 2018 ) and positively affected student knowledge, performance, and clinical judgment skills ( Chen et al, 2020 ; Fogg et al, 2020 ; Sapiano et al, 2018 ). Taken together, our findings indicate that VS learning is a potentially valuable method of providing nursing education for students, even those with limited English proficiency, especially during a pandemic when safe clinical placement is not attainable.…”
Section: Discussionmentioning
confidence: 98%
“…Participants reported that VS was beneficial in helping them practice and gain competence and confidence to provide nursing care. Other studies have reported that VS offered students a positive experience ( Gu et al, 2017 ; Wright et al, 2018 ) and positively affected student knowledge, performance, and clinical judgment skills ( Chen et al, 2020 ; Fogg et al, 2020 ; Sapiano et al, 2018 ). Taken together, our findings indicate that VS learning is a potentially valuable method of providing nursing education for students, even those with limited English proficiency, especially during a pandemic when safe clinical placement is not attainable.…”
Section: Discussionmentioning
confidence: 98%
“…Determining how, where, and why technology like AI should be used to support practice is of immediate interest and a growing competency requirement in health sciences and informatics education 43. Nursing education should evolve its competencies and curriculums proactively for the increasing use of digital technologies in all areas of practice39 while incorporating novel pedagogical approaches—for example, immersive technologies such as virtual and augmented reality—to deliver aspects of simulation based education 4445…”
Section: Reform Nursing Educationmentioning
confidence: 99%
“…Educators are eager to provide students with engaging ways to learn, and VR provides a medium to explore virtual scenarios and make meaning through virtual experiences (Castaneda et al, 2017). Research from a variety of fields has demonstrated the value of virtual simulations for learning information and skills as a result of immersion (Chen et al, 2020;Chernikova et al, 2020;Harman et al, 2017;Kaplan et al, 2021;Krokos et al, 2019;Pantelidis, 2010). Immersive VR enables students to physically engage with new concepts and environments (Bailenson, 2018;Hu-Au & Lee, 2017;Lau & Lee, 2015;Prensky, 2013;Regian et al, 1992;Roussou & Slater, 2005;Winn, 1993), leads to a deeper sense of presence and engagement in real or surreal environments (Coelho et al, 2006;Heeter, 1992;Makransky & Lilleholt, 2018), and thus likely enables them to more actively construct their own knowledge (Koohang et al, 2009;Roussou & Slater, 2005).…”
Section: Literature Reviewmentioning
confidence: 99%